METHODOLOGICAL PRINCIPLE OF FORMATION OF MAIN LITHOTYPES DATABASE FOR DETERMINATION OF EARTH CRUST COMPOSITION OF NORTH-WEST REGION OF UKRAINIAN SHIELD BY SEISMOGRAVITATIONAL METHOD - PRODAIVODA, G.; ZINCHENKO, O.; KOZIONOVA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Methodological principles of fonnation of main lithotypes database for north-west region of Ukrainian shield for solution for deep mapping task of rock associations based on seismogravitational method have been developed. Main lithotypes of region and their chemical and mineralogical composition have been identified. Estimation of reliability of calculation of chemical composition by petochemical method has been implement.